The marginal fit of lithium disilicate crowns: Press vs. CAD/CAM - Azar, Basel; Eckert, Steve; Kunkela, Josef; Ingr, Tomaš; Mounajjed, Radek (Brazilian oral research, 2018)
This study aimed to compare the vertical marginal gap of teeth restored with lithium disilicate crowns fabricated using CAD/CAM or by pressed ceramic approach. Twenty mandibular third molar teeth were collected after surgical extractions and prepared to receive full veneer crowns. Teeth were optically scanned and lithium disilicate blocks were used to fabricate crowns using CAD/CAM technique. Polyvinyl siloxane impressions of the prepared teeth were made and monolithic pressed lithium disilicate crowns were fabricated. The marginal gap was measured using optical microscope at 200× magnification (Keyence VHX-5000, Japan). Statistical analysis was performed using Wilcoxon test. The lithium disilicate pressed crowns had significantly smaller (p = 0.006) marginal gaps (38 ± 12 μm) than the lithium disilicate CAD/CAM crowns (45 ± 12 μm). This research indicates that lithium disilicate crowns fabricated with the press technique have measurably smaller marginal gaps compared with those fabricated with CAD/CAM technique within in vitro environments. The marginal gaps achieved by the crowns across all groups were within a clinically acceptable range.
Keywords: Dental Porcelain; zubní porcelán; Dental Prosthesis Design; Reference Standards; Dental Marginal Adaptation; design s pomocí počítače; zubní korunky; Reproducibility of Results; zubní marginální adaptace; lidé; Computer-Aided Design; referenční hodnoty; neparametrická statistika; Materials Testing; reprodukovatelnost výsledků; referenční standardy; zubní protéza - design; Dental Impression Technique; Reference Values; Crowns; zubní technika otisková; testování materiálů; Dental Impression Materials; Statistics, Nonparametric; materiály pro zubní otisky; Humans